Determinants of Healthcare Utilization among Coastal Communities in Sinjai Regency - Muhammad Ilyas; Muh Rusdi; Adi Hermawan (PT. Nasyah Medika Care, 2025)
Background: Coastal communities experience multiple barriers that may restrict healthcare utilization despite insurance coverage and healthcare facilities. Research Objective: This study analysed determinants of healthcare utilization among coastal communities in Sinjai Regency, South Sulawesi, Indonesia. Methods: A cross-sectional study involved 61 respondents selected through proportionate stratified random sampling from coastal and island areas. Data were collected using a validated questionnaire based on Andersen’s Behavioral Model. Descriptive statistics, chi-square tests, and multiple binary logistic regression were applied, with significance established at p<0.05. Results: Overall, 62.3% of respondents used formal healthcare services when needed. Bivariate analysis identified associations with knowledge, cultural beliefs, JKN membership, distance, transportation, family support, perceived service quality, healthcare need, and chronic disease. Multivariate analysis showed that transportation availability was the strongest determinant (AOR=4.38), followed by active JKN membership (AOR=4.16), high perceived healthcare need (AOR=3.91), and good health knowledge (AOR=3.72). The model explained 52.2% of utilization variation. Conclusion: Equitable healthcare utilization requires accessible transportation, active insurance membership, health knowledge, and recognition of healthcare needs. Coastal health strategies should integrate transportation support, JKN assistance, outreach services, preventive screening, and context-sensitive health education.